Strategic Optimization of LMS in Higher Education for Working-Class Students Using SWOT Analysis - Widarini, Wari; Abdullah, Fadil; Anggara, Ikbal (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The implementation of Learning Management Systems (LMS) in higher education presents challenges for working-class students who must balance their studies and employment. At Private University X in Karawang, the transition from conventional learning methods to LMS has caused adaptation difficulties for both students and lecturers, potentially hindering learning effectiveness. Therefore, an evaluation is necessary to identify key aspects for LMS optimization based on strategies aligned with the university’s specific conditions and needs. This study formulates LMS optimization strategies through a survey involving lecturers and students from the Industrial Engineering Department. Data were collected between February 15 and March 8 and analyzed using the SWOT method based on the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS). The analysis involved developing variables through interviews validated by previous research, followed by a structured survey to determine variable weights used in quadrant analysis, which were subsequently revalidated by respondents. The findings indicate that diversification is the most effective strategy, as identified through quadrant analysis with an internal factor score of 0.76 and an external factor score of -9.7. This strategy includes personalized learning to align content with student needs, AI integration for enhanced interaction and recommendations, gamification to boost engagement, and improved technical support to address LMS related challenges. By providing a structured strategic framework, this study offers practical guidance for higher education institutions in developing LMS solutions that are more adaptive, inclusive, and aligned with lecturer and student demands.